Development of a liquid chromatography high resolution mass spectrometry method for the quantitation of viral envelope glycoprotein in Ebola virus-like particle vaccine preparations. Issue 1 (December 2016) - Cazares, Lisa; Ward, Michael; Brueggemann, Ernst; Kenny, Tara; Demond, Paul; Mahone, Christopher; Martins, Karen; Nuss, Jonathan; Glaros, Trevor; Bavari, Sina
Abstract Background Ebola virus like particles (EBOV VLPs, eVLPs), are produced by expressing the viral transmembrane glycoprotein (GP) and structural matrix protein VP40 in mammalian cells. When expressed, these proteins self-assemble and bud from 'host' cells displaying morphology similar to infectious virions. Several studies have shown that rodents and non-human primates vaccinated with eVLPs are protected from lethal EBOV challenge. The mucin-like domain of envelope glycoprotein GP1 serves as the major target for a productive humoral immune response. Therefore GP1 concentration is a critical quality attribute of EBOV vaccines and accurate measurement of the amount of GP1 present in eVLP lots is crucial to understanding variability in vaccine efficacy. Methods After production, eVLPs are characterized by determining total protein concentration and by western blotting, which only provides semi-quantitative information for GP1 . Therefore, a liquid chromatography high resolution mass spectrometry (LC-HRMS) approach for accurately measuring GP1 concentration in eVLPs was developed. The method employs an isotope dilution strategy using four target peptides from two regions of the GP1 protein. Purified recombinant GP1 was generated to serve as an assay standard. GP1 quantitation in 5 eVLP lots was performed on an LTQ-Orbitrap Elite and the final quantitation was derived by comparing the relative response of 200 fmol AQUA peptide standards to the analyte response at 4 ppm. Results Conditions were optimized to ensure complete tryptic digestion of eVLP, however, persistent missed cleavages were observed in target peptides. Additionally, N-terminal truncated forms of the GP1 protein were observed in all eVLP lots, making peptide selection crucial. The LC-HRMS strategy resulted in quantitation of GP1 with a lower limit of quantitation of 1 fmol and an average percent coefficient of variation (CV) of 7.6 %. Unlike western blot values, the LC-HRMS quantitation of GP1 in 5 eVLP vaccine lots exhibited a strong linear relationship (positive correlation) with survival (after EBOV challenge) in mice. Conclusions This method provides a means to rapidly determine eVLP batch quality based upon quantitation of antigenic GP1 . By monitoring variability in GP1 content, the eVLP production process can be optimized, and the total amount of GP1 needed to confer protection accurately determined.